The progress of pupils in their first school year across classes and educational systems. (21st July 2014) - Tymms, Peter; Merrell, Christine; Wildy, Helen
<x xml:space="preserve">Abstract</x> Educational effectiveness research has identified school membership as being and important factor in relation to academic progress but it has also pointed to the importance of teachers. Additionally, districts have been shown to be of minor importance for progress once key variables are taken into account while data from international studies suggest that countries are important when attainment is studied while controlling for background factors. A perspective, named the Proximate Variables within Jurisdictions (PVJ) theory, is introduced to help understand and predict relationships. The theory holds that variables which are closest to the student are the most influential but that the jurisdiction where the student is educated, which has its own approaches to education and upbringing is of similar importance. A child's educational success in international terms is most influenced by actions in the home and the classroom seen in the context of the country where she or he is brought up. Does the theory hold when progress in classrooms, year groups and educational systems (jurisdictions) is estimated in a single analysis? This study compared progress of pupils in over 4000 classrooms across 11 educational systems. Large differences were found between classes and the educational systems both for reading and mathematics during the first year at school. The theory holds for the most part but questions are left unanswered and the paper sets out a series of testable hypotheses which may be addressed in the future.